Diagnosis and instructional remediation amongst learners with developmental dyscalculia in number and numeration - Wonu, Nduka; Nwoko, Osalumese Onuoma (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
The study is an educational intervention to improve the learning outcomes of junior secondary students with Developmental Dyscalculia (DD) in Number and Numeration (NAN) using the Collaborative Learning Model (CLM) in Port Harcourt Local Government Area (LGA). A quasi-experimental design was adopted in the study. A total of 68 Junior Secondary Class 2 (JSC2) students with DD in Number and Numeration took part in the study. Two randomly selected junior secondary schools were used for this study. One school was assigned to the experimental group, whereas the other was assigned to the control group. The processes of the diagnosis, identification, and selection of students with DD for participation in the study involved three phases, viz: The use of existing school results, administration of the Developmental Dyscalculia Diagnostic Test (3DT) and Teachers' judgments. The Number and Numeration Performance Test (NANPT). The NANPT was used to measure the performance of the students in NAN. Experts in Mathematics Education validated the instruments, and Kuder-Richardson, KR-21 was used to ascertain the reliability of the instruments, which gave indices of 0.87 and 0.84 for NANPT and 3DT respectively. The students in the experimental group learned NAN using the CLM whereas those in the control group were taught the same topics using the Traditional Teaching method (TTM). Two research questions and two hypotheses guided the study. The mean, standard deviation and Analysis of Covariance (ANCOVA) were used for data analysis. The result established that the CLM was more effective than the TTM in advancing the performance of students with DD in Number and Numeration . The students did not differ significantly in their performance in NAN based on gender. It was recommended, among others, that mathematics teachers should employ CLM in their classroom teaching and ensure that all students participate and cooperate effectively with one another to enhance student-learning outcomes.